รูปแบบการมีส่วนร่วมในการประชาสัมพันธ์ของมหาวิทยาลัยเทคโนโลยีราชมงคลศรีวิชัย - ไกรนรา ฝนทิพย์; Lertgrai, Punya; Saijun, Krittaporn Saengae (Academic Journal Phranakhon Rajabhat University, 2017)
The research objectives were to study the status of participation in Public Relations, to develop the participation model in Public Relations and to evaluate participation model in Public Relations of Rajamangala University of Technology Srivijaya. The quantitative analysis using Percentage, mean, standard variation and the qualitative analysis using the lessons learned by the model ALM, AAR and evaluation forms using CIPP Model. The research result as follow; 1. The participation in Public Relations of Rajamangala University of Technology Srivijaya is moderate level. The highest level was the awareness of the public relations activities. 2. The model of participatory public relations of Rajamangala University of Technology Srivijaya should consist of 4 procedure’s in POPE Model; P is Planing, O is Operation, P is Perception, and E is Evaluation. 3. The participation model in public relations of Rajamangala University of Technology Srivijaya can apply in the university.